Kajian Keilmuan Islam Holistik-Integratif Mengakhiri Dikotomi Ilmu Agama dan Umum - Yaqin, Fuad Ngainul; Muzayin Shofwan, Arif; Rohman, miftakhul (SINDA: Comprehensive Journal of Islamic Social Studies, 2023)
Along with the development of science and technology, the construction of Islamic scholarship continues to change from time to time. In every era, there must always be a renewal in constructing Islamic scholarship so that it is not left behind with the progress of the times. Research with this literature study resulted in the following conclusions. First, until now the construction of Islamic scholarship has passed through three stages, namely: traditionalism which is characterized by normative-theological, modernism which is empirical-sociological, and postmodernism which is characterized by holistic-integrative Second, the current era of postmodernism is an era of seeking the right form or model for ending the dichotomy of religion and general science. Third, the era of holistic-integrative Islamic scientific postmodernism is classified in the humanities sciences (al-ilmu al-insaniyah) which includes, among others; sociology, anthropology, psychology, history, social institutions, Basic Natural Sciences, Basic Cultural Sciences, and Basic Social Sciences, which are presented with a scientific approach. Thus, holistic-integrative Islamic scholarship in the current era of postmodernism must include these humanities sciences in Islamic scientific disciplines to be able to answer and face the development of an increasingly globalized era.